KAJIAN TENTANG METODE PERSAMAAN RICCATI PROYEKTIF - Fitri Yessi Jami (Jurusan Matematika FMIPA Universitas Andalas Padang, 2018)
Abstract. In this paper, we discuss the derivation and application of a projective Riccatiequation method in solving nonlinear partial dierential equations. We also study themathematical aspects of the method and its limitations in some particular cases.Kata Kunci: Nonlinear partial dierential equations, projective Riccati equation method,dominant balance principle